“Utux Tmninun U, ini sruwa muway pusu dnui rudan sunan ka hiya”: Reading Naboth’s Refusal (1 Kings 21:3) from the Sediq Mother Tongue - Risaw Walis (Noyam Publishers, 2021)
Since the advent of the vernacular Bibles for the Taiwan Indigenous Peoples (TIP), the TIP Christians are privileged to read and hear the Word of God in their ‘ancestral tones’ with familiarity and attachment. Sediq people, the nation the author belongs to, have also been privileged from the publication of the vernacular Bible. Most Sediq people are welcoming this vernacular Bible and feel blessed to use their ancestor’s language to communicate with God. However, the scarcely discussed issues are that the biblical reading and interpretive approaches employed by the Sediq people are distinctive. Namely, Sediq people’s vernacular involves Sediq’s cultural resources-philology, traditional narratives, traditional stories, cultural meanings, traditional philosophies and worldviews-into the interaction with the contents and stories of the vernacular Bible. This paper argues the significance of embracing vernacular as a foundation for biblical reading, how this acceptance shifts the role of the vernacular Bible and how this approach contributes to the contextual, decolonial and postcolonial reflections on the TIP’s land issues by reading 1 Kings 21:3, one of the verses that resonating TIP’s ancestral and cultural wisdom.